Sosialisasi Pengelolaan Cedera Melalui Masase - Ningsih, Yuni Fitriyah; Wisnu, Hari; Hartoto, Setiyo; Yulfadinata, Afifan; Arief, Nur Ahmad (Laksana Olahraga, 2024)
Sports injuries are a common issue faced by athletes and individuals who are physically active, which can hinder performance and affect quality of life. Effective management and prevention of injuries are crucial in sports, and masase has been recognized as a beneficial method in this regard. This study aims to socialize the techniques of managing sports injuries through masase as a therapeutic intervention. The methods used in this study include providing counseling and training in masase techniques to teachers of the MGMP PJOK SMP in Nganjuk Regency. The results of this socialization are expected to enhance participants' knowledge and skills in managing sports injuries more effectively, as well as to have a positive impact on recovery and injury prevention. This outreach demonstrates that socializing masase as part of a sports injury management strategy can provide participants with knowledge on the prevention and recovery processes for athletes or students before and after physical activities.